2024
DOI: 10.7150/ijms.92131
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiota as a Potential Risk Factor for Coronary Artery Disease in Diabetes: A Two-Sample Bi-Directional Mendelian Randomization Study

Zhaopei Zeng,
Junxiong Qiu,
Yu Chen
et al.

Abstract: The current body of research points to a notable correlation between an imbalance in gut microbiota and the development of type 2 diabetes mellitus (T2D) as well as its consequential ailment, coronary artery disease (CAD). The complexities underlying the association, especially in the context of diabetic coronary artery disease (DCAD), are not yet fully understood, and the causal links require further clarification. In this study, a bidirectional Mendelian randomization (MR) methodology was utilized to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The findings revealed that the intestinal family Oxalobacteraceae significantly increased compared with the control group ( Costabile et al, 2022 ). Another MR analysis demonstrated that an increased presence of the family Oxalobacteraceae was associated with the risk of T2DM ( Zeng et al, 2024 ). Studies have shown that the therapeutic effects and side effects of metformin are closely related to changes in intestinal flora ( Forslund et al, 2017 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that the intestinal family Oxalobacteraceae significantly increased compared with the control group ( Costabile et al, 2022 ). Another MR analysis demonstrated that an increased presence of the family Oxalobacteraceae was associated with the risk of T2DM ( Zeng et al, 2024 ). Studies have shown that the therapeutic effects and side effects of metformin are closely related to changes in intestinal flora ( Forslund et al, 2017 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that the intestinal family Oxalobacteraceae significantly increased compared with the control group (Costabile et al, 2022). Another MR analysis demonstrated that an increased presence of the family Oxalobacteraceae was associated with the risk of T2DM (Zeng et al, 2024). Studies have shown that the therapeutic effects and side effects of metformin are closely related to changes in intestinal flora (Forslund et al, 2017;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that the intestinal family Oxalobacteraceae significantly increased compared with the control group (Costabile et al, 2022). Another MR analysis demonstrated that an increased presence of the family Oxalobacteraceae was associated with the risk of T2DM (Zeng et al, 2024). Studies have shown that the therapeutic effects and side effects of metformin are closely related to changes in intestinal flora (Forslund et al, 2017;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%